ANALYSIS OF BONE IMPLANT TO CONTACT VALUE USING SCANNING ELECTRON MICROSCOPE IN POST IMMEDIATE IMPLANTS WITH ADDITION OF GEL-EXTRACTED ROSELLA FLOWER - DHARMAUTAMA, MOHAMMAD; THALIB, BAHRUDDIN; SUSANIAWATY, YULI; DAMMAR, IRFAN; MIR, ANDI ADYTHA (International Journal of Applied Pharmaceutics, 2019)
Objective: The objective of the study was to analyze the difference of bone to implant contact (BIC) value post-immediate implants with or without injecting rosella flower extracts gel in mongrel. Methods: A total of 18 implants were inserted in 9 mongrel’s dog. The implant was divided into two groups. The first one (test implant) was implanted immediately after injection of gel-extracted rosella flower 10%, while another group (control implant) was implanted immediately after the tooth extraction. The histomorphometry analysis was done after 14, 28, and 56 days to find out the BIC value. Result: The mean value of BIC rosella group was 63.44% and the mean value of the control group was 52.11%, with p=0.041. Conclusion: Rosella flower extract is able to shorten the inflammatory phase after implantation, accelerate and expand bone growth by spurring collagen deposition as well as inhibiting osteoclast activity.